Trend of physical activity surveillance among female varsity students on activity daily lifestyle / Muhammad Hazeem Mustaffar Kamal - Mustaffar Kamal, Muhammad Hazeem (Faculty of Sport Science and Recreation, 2020)
The purpose of this study is to identify the trend of physical activity among female varsity students on activity daily lifestyle for past 7 days. 261 respondents are recruited into this study from the University College of Yayasan Pahang which is five faculty are involved. International Physical Activity Questionnaires was using in this study to identify the most spend female varsity students involved in physical activity. The component involved in IPAQ are assessed by low physical activity, moderate physical activity, vigorous physical activity. The statistical analysis using for this study are conducted by using One - Way ANOVA. There was a significant trend of low, moderate and vigorous physical activity level among female varsity students on activity daily lifestyle for past 7 days which is p <0.01 and then the null hypothesis was rejected. Hence, it was concluded that female varsity students are mostly involved in high intensity compare to low or moderate physical activity level.